2010
DOI: 10.1016/j.scitotenv.2010.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Presence and fate of priority substances in domestic greywater treatment and reuse systems

Abstract: A wide range of household sources may potentially contribute to contaminant loads in domestic greywater. The ability of greywater treatment systems to act as emission control barriers for household micropollutants, thereby providing environmental benefits in addition to potable water savings, have not been fully explored. This paper investigates the sources, presence and potential fate of a selection of xenobiotic micropollutants in on-site greywater treatment systems. All of the investigated compounds are lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 29 publications
1
17
0
3
Order By: Relevance
“…Existing greywater treatment systems show a wide range of design principles and sophistication, from simple single-household soil filter systems to more elaborate community-scale multi-stage rotating biological contact (RBC) reactors, constructed wetlands and membrane bioreactors, amongst others -all based on chemical, physical and biological processes such as settling, filtration, adsorption, aeration, precipitation, aerobic/anaerobic digestion, and disinfection (Donner et al, 2010;Ghunmi et al, 2011). The choice of a grey water treatment system includes considering different treatment steps that may be applied, depending on the required quality of the effluent .…”
Section: Introductionmentioning
confidence: 99%
“…Existing greywater treatment systems show a wide range of design principles and sophistication, from simple single-household soil filter systems to more elaborate community-scale multi-stage rotating biological contact (RBC) reactors, constructed wetlands and membrane bioreactors, amongst others -all based on chemical, physical and biological processes such as settling, filtration, adsorption, aeration, precipitation, aerobic/anaerobic digestion, and disinfection (Donner et al, 2010;Ghunmi et al, 2011). The choice of a grey water treatment system includes considering different treatment steps that may be applied, depending on the required quality of the effluent .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Eriksson et al (2002;2003) and Palmquist and Hanaeus (2005) have collectively shown that a large number of xenobiotic substances can find their way into greywater via bathroom and laundry products. Donner et al (2010) have reported initial investigations into the fate of a range of pollutants within greywater treatment and reuse systems. However, given the increasing implementation of greywater recycling technology, it is evident that additional research to elucidate the behavior of xenobiotic micropollutants during greywater treatment would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Charakteryzuje je jednak znaczna zawartość związków organicznych, co wymusza na potencjalnych eksploatatorach instalacji wykorzystania ścieków szarych zastosowanie układów do ich podczyszczania. Dodatkowo stężenie poszczególnych substancji zanieczyszczających ścieki szare warunkowane jest tym, gdzie powstają [8]. Charakterystykę ścieków pochodzących z różnych źródeł przedstawiono w tabeli 2.…”
Section: Wprowadzenieunclassified
“…Charakterystykę ścieków pochodzących z różnych źródeł przedstawiono w tabeli 2. Stężenie zanieczyszczeń obecnych w ściekach szarych odprowadzanych z poszczególnych urządzeń sanitarnych może zmieniać się w szerokim zakresie [8], jednakże za najbardziej zanieczyszczone uznać można medium pochodzące z kuchni. Zawiera ono często oleje oraz inne niekorzystne substancje, których obecność w ściekach szarych dyskwalifikuje ich zastosowanie do spłukiwania misek ustępowych czy podlewania ogrodu, co powoduje, iż zazwyczaj nie są one wykorzystywane [7].…”
Section: Wprowadzenieunclassified